PENGARUH VARIASI ABU SEKAM DAN BENTONIT PADA CETAKAN PASIR TERHADAP KEKERASAN DAN STRUKTUR MIKRO 2) 1) HASIL CORAN ALUMUNIUM AA 1100 - Tarkono, .; Supriadi, Harnowo; Sewandono, Doni (Jurnal Ilmiah Teknik Mesin FEMA, 2013)
The aim of this research is to know the physical and mechanical properties of aluminum casting results printed by using sand mold. Variation is made on the formation of mold sand where there happens a difference of the addition of binding substance rice husk ash and bentonite have been blended into a sand mould-forming composition. The Material used in this study is aluminum with purity levels above 99, which melted in the kitchen Dipper Krusible type and printed in sand mold. The tools which are used in testing hardness and micro-structure of tests in a row are: brinell hardness test and olympus metallurgical microscope.  Brinell hardness testing uses the test with the standard ASTM E 10-01 and micro testing structure uses standard ASTM E 3 by way of looking at the specimen under a microscope. From this data, it can be obtained that the lowest hardness calculation of test results of 17.7636 HBW for compositions that vary on a mixture of bentonite and ash 6% husk 14%, and the maximum calculation of the hardness is obtained on the composition of the mixture of 10% and 8% bentonite husk ash, where the calculation of the hardness of 22.8100 HBW. In micro structure testing; looks that porosity in aluminum in great numbers when a comparison between bentonite and binding substance grey husk in the levels are quite different, causing the result of casting have much number of porosity, so that it causes the low level of the hardness. While  for the comparison of levels of grey husk and bentonite which approach the same levels, When added to the composition of the sand mould-forming, micro structure test results showed that metal casting results have little amount of porosity causing aluminum castings results have a high level of hardness. Keywords : sand mold, porosity, hardness calculation, micro structure.